Protective effect of Nigella sativa and thymoquinone on serum/glucose deprivation-induced DNA damage in PC12 cells - Beheshteh Babazadeh; Hamid Reza Sadeghnia; Elham Safarpour Kapurchal; Heydar Parsaee; Sima Nasri; Zahra Tayarani-Najaran (Mashhad University of Medical Sciences, 2012)
Objective: The discovery and development of natural products with potent antioxidant properties has been one of the most interesting and promising approaches in the search for treatment of CNS injuries. The most significant consequence of the oxidative stress is thought to be the DNA modifications, which can become permanent via the formation of mutations and other types of genomic instability resulting cellular dysfunction. Serum/glucose deprivation (SGD) has served as an excellent in vitro model for the understanding of the molecular mechanisms of neuronal damage during ischemia and for the development of neuroprotective drugs against ischemia-induced brain injury. Nigella sativa (N. sativa) seeds and thymoquinone (TQ), its most abundant constituent, have been shown to possess anti-inflammatory, antioxidant, chemopreventive and anti-neoplastic effects both in vitro and in vivo. Therefore, in this study we investigated genoprotective effects of N. sativa and TQ on DNA damage of PC12 cells under SGD condition. Materials and Methods: PC12 cells were cultured in DMEM medium containing 10% (v/v) fetal bovine serum, 100 units/ml penicillin, and 100 µg/ml streptomycin. Initially cells were pretreated with different concentrations of N. sativa extract (NSE), (10, 50, 250 µg/ml) and TQ (1, 5, 10 µg/ml) for 6 h and then deprived of serum/glucose (SGD) for 18 h. The alkaline comet assay was used to evaluate the effect of these compounds on DNA damage following ischemic insult. The amount of DNA in the comet tail (% tail DNA) was measured as an indicator of DNA damage. Results: A significant increase in the % tail DNA was seen in nuclei of cells following SGD induced  DNA damage (p0.05). NSE and TQ pretreatment resulted in a significant decrease in DNA damage following ischemic insult (p